Matell 2006 Sediment Dynamics Between the Glacier Linnébreen and its Lake Linnévatnet in the European High Arctic (Arctic Data Center, 2013)
Nora studied the processes associated with sediment flux down the Linne' meltwater system during the summer of 2005. She related suspended sediment load to weather parameters, glacier ablation and river stage/discharge